POLA MUSIM DAN DAERAH PENANGKAPAN RAJUNGAN (Portunus pelagicus) DI PERAIRAN KABUPATEN PANGKEP (Season And Patterns of Catching Swimming Crab (Portunus pelagicus) in Pangkep Waters Regency) - . Ihsan; Eko Sri Wiyono; Sugeng Hari Wisudo; John Haluan (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2014)
ABSTRACTThe season patern of swimming crab is influenced by rekruitman amount generated by each individual crab in the fishing ground. This study aims to assess the pattern of fishing crab season and the fishing ground as a participatory method in Pangkep water Regency. The data collected consisted of primary and secondary data. Data analysis was performed using the technique of time series analysis on the catch per unit of fishing effort crab monthly during the last six years. The peak season is catching crabs at IMP> 1% which took place in June and September. The highest percentage of catches in the fishing ground is in September which is 11.71% and lowest in April which amounted to 5.77%. The results of the analysis of index fishing season of crabs is throughout the year at the fishing area in Pangkep waters.Keywords: Analysis, Season Patern, Fishing Ground, Swimming Crabs-------ABSTRAKPola musim rajungan dipengaruhi oleh jumlah rekruitman yang dihasilkan oleh setiap individu rajungan di daerah penangkapan. Penelitian ini bertujuan untuk mengkaji pola musim penangkapan rajungan dan daerah penangkapan rajungan secara partisipatif di perairan Kabupaten Pangkep. Data yang dikumpulkan terdiri dari data primer dan data sekunder. Analisis data yang dilakukan adalah menggunakan teknik analisis deret waktu (time series) terhadap hasil tangkapan per satuan upaya penangkapan bulanan rajungan selama enam tahun terakhir. Musim puncak penangkapan rajungan berada pada IMP > 1 % yakni berlangsung pada bulan Juni dan September. Persentase tangkapan tertinggi di daerah penangkapan adalah pada bulan September yakni 11,71 % dan terendah pada bulan April yakni sebesar 5,77 %. Hasil analisis indeks musim penangkapan (IMP) rajungan dilakukan sepanjang tahun di daerah penangkapan di perairan Kabupaten Pangkep.Kata kunci: Analisis; Pola Musim; Daerah Penangkapan; Rajungan